Targeted Therapy for RET Fusion Lung Cancer: Breakthrough and Unresolved Issue - Takamori, Shinkichi; Matsubara, Taichi; Haratake, Naoki; Toyokawa, Gouji; Fujishita, Takatoshi; Toyozawa, Ryo; Ito, Kensaku; Yamaguchi, Masafumi; Taguchi, Kenichi; Okamoto, Tatsuro; Seto, Takashi (Frontiers in Oncology, 2021)
Molecular drugs targeting mutated or rearranged oncogene drivers have become one of the standard recognized treatments in patients with advanced and recurrent non-small-cell lung cancer. RET is located in the long arm of human chromosome 10 and encodes a receptor tyrosine kinase protein, and RET fusion-positive lung adenocarcinoma occurs in 1–2% of cases. Clinical trials of multikinase inhibitors, including cabozantinib, vandetanib, sorafenib, and lenvatinib, that inhibit RET oncogene activity have shown their antitumor efficacy. Recently, RET inhibitors such as pralsetinib and selpercatinib that are specialized for RET kinase have also been developed and their efficacy was investigated in previous clinical trials (BLU-667, LOXO-292). In this review, we summarized the effects and adverse events of multikinase and selective RET inhibitors and the various diagnostic techniques for RET gene fusion. In the perspective part, we focused on the unsolved issues on treatment for RET fusion-positive lung cancer and future developments.